Membangun Karakter Siswa melalui Bimbingan Konseling: Teknik-Teknik Berbasis Nilai-Nilai Islam - Muhamad Latief Khana; Yunia Khaira; Vani Sintia Anabila; Hidayani Syam (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The point of this investigate is to recognize counseling direction strategies based on Islamic values, analyze the impact of executing Islamic-based counseling direction on the arrangement of understudy character. Give down to earth proposals for instructors and counselors in actualizing Islamic values in schools. The inquire about strategy we utilize is the library strategy. This investigate employments library investigate (Library Investigate), library investigate here points to gather data and data with the assistance of different materials found within the library room. To discover the information required in this dialog, the creator collected books related to the issue beneath consider. The information sources in this inquire about are books related to counseling direction which claim to construct understudy character through counseling methods: Methods based on Islamic values. The comes about and conclusions of this inquire about are to discover out and give counsel to direction and counseling instructors whose students' character is as of now exceptionally missing through counseling direction where this inquire about employments strategies based on Islamic values.